2020
DOI: 10.3390/separations7010013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Cryogen-Free Thermal Modulation-Based Comprehensive Two-Dimensional Gas Chromatography-Time-of-Flight Mass Spectrometry (GC×GC-TOFMS) for the Qualitative Analysis of a Complex Bitumen Sample

Abstract: Historically, one-dimensional gas chromatography combined with mass spectrometry (GC/MS) has been employed in the analysis of petrochemical samples such as diesel, crude oil and bitumen. With increasingly complex samples, obtaining detailed information can be difficult with this method due to the large number of coelutions. By implementing comprehensive two-dimensional gas chromatography time-of-flight mass spectrometry (GC×GC-TOFMS), the limitations of GC/MS can be overcome, due to the ability of this method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The instrument also has a provision for an auxiliary gas flow at the modulation stage, so that faster release of analytes can be achieved [37], so that it may also be classified as a hybrid modulator. Boswell et al [38] compared the performance of the SSM with conventional coolant-driven modulation for bitumen samples, using a constant mass-flow range through the two ( 1 D and 2 D) columns, both with an id of 250 μm. They found a similar performance for the two types of modulators.…”
Section: Progress In Thermal Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument also has a provision for an auxiliary gas flow at the modulation stage, so that faster release of analytes can be achieved [37], so that it may also be classified as a hybrid modulator. Boswell et al [38] compared the performance of the SSM with conventional coolant-driven modulation for bitumen samples, using a constant mass-flow range through the two ( 1 D and 2 D) columns, both with an id of 250 μm. They found a similar performance for the two types of modulators.…”
Section: Progress In Thermal Modulationmentioning
confidence: 99%
“…Boswell et al. [38] compared the performance of the SSM with conventional coolant‐driven modulation for bitumen samples, using a constant mass‐flow range through the two ( 1 D and 2 D) columns, both with an id of 250 μm. They found a similar performance for the two types of modulators.…”
Section: Modulationmentioning
confidence: 99%
“…Most profiling of terpenes and terpenoids in cannabis utilize conventional one-dimensional gas chromatography (GC) [18][19][20][21]. While this has been broadly helpful in discovering and quantifying the molecules in cannabis, GC can co-elute compounds in a complex mixture, resulting in poor or no identification or an incorrect calculation of their abundance [22]. Two-dimensional gas chromatography (GC × GC) is a powerful technique that provides better separation of the compounds in a second, chemically orthogonal dimension [23].…”
Section: Introductionmentioning
confidence: 99%
“…For such a purpose, a dedicated trapping column was employed, which being characterized by joining two pieces of uncoated column to each end of a porous layer open tubular column. Boswell et al used the SSM within the context of group type and biomarker analysis of Alberta oil sands bitumen [13]. An et al reported the use of the SSM within the context of quartz filter-based thermal desorption aerosol GC × GC-MS [14].…”
Section: Introductionmentioning
confidence: 99%